Hubungan Pola Asuh Otoriter Dan Kecerdasan Emosional Dengan interaksi Teman Sebaya Anak Usia 4-5 Tahun - Melati Retnandhia Putri (Prosiding University Research Colloquium, 2021)
Peer interaction is a relationship that exists between a group of children with limitedmembership, which influence each other, which is influenced by various factors. Factorsthat may influence peer interaction in early childhood are parenting styles and emotionalintelligence. The purpose of this study was to determine the effect of authoritarianparenting and emotional intelligence with peer interaction.The variables used in thisstudy are Authoritarian Parenting ( ), Emotional Intelligence ( ) and peerinteraction (Y). The population in this study is TK BA in Mungkid District, there are 20schools with 331 class A students. The sample in this study was 3 BA Kindergartenschools, namely BA Need, BA Bumirejo 1, BA Bumirejo 2 with a group A of 30 students.The sampling technique used is purposive sampling. Methods of data collection usingquestionnaires and observation techniques. The data analysis technique used multiplelinear regression test.The results of the study concluded that there is an influencebetween authoritarian parenting and emotional intelligence with peer interaction eitherpartially or simultaneously. Partially proven by the acquisition of the t-count value ofauthoritarian parenting of 4.496 with a sig. 0.000 < 0.05, emotional intelligence alsoobtained a t-count value of 2.312 with a sig value. 0.029 < 0.05. Simultaneously proved bythe acquisition of a calculated F value of 58.716 with a sig value. 0.000 which means thatthe variables of authoritarian parenting and emotional intelligence together affect peerinteraction for early childhood.